Analisis Isi Pesan Dakwah dalam Novel “Tinta Terakhir” Karya Narandara - Astri Syahputri, Siti Novi; Nurhanifah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The rapid development of technology and communication in this modern era influences the way da'i (preachers) convey da'wah messages to mad'u (listeners or recipients of da'wah). In this case, the use of various da'wah media, such as print, electronic and digital media, is a necessity as well as an effective strategy to attract the attention of mad'u. One effective method for conveying da'wah messages is through print media such as novels. Novels are unique in their literary sentences which are able to compete with other media in terms of popularity and effectiveness in conveying da'wah messages. This research aims to find out the da'wah messages contained in the novel "Ink Last" by Narandara. The research uses a qualitative content analysis method, with data taken from dialogue excerpts in the novel. The results of the research showed that there were 25 da'wah messages consisting of 4 aqidah messages (1 faith in Allah and 3 faith in qada and qadar), 8 messages regarding sharia including worship (7 prayers and 1 reading the Koran), and 13 messages regarding morals (6 morals towards Allah, 4 morals towards fellow humans, and 3 morals towards family).